Ocular lens morphology is influenced by ecology and metamorphosis in frogs and toads. Issue 1987 (30th November 2022) - Mitra, Amartya T.; Womack, Molly C.; Gower, David J.; Streicher, Jeffrey W.; Clark, Brett; Bell, Rayna C.; Schott, Ryan K.; Fujita, Matthew K.; Thomas, Kate N.
Abstract : The shape and relative size of an ocular lens affect the focal length of the eye, with consequences for visual acuity and sensitivity. Lenses are typically spherical in aquatic animals with camera-type eyes and axially flattened in terrestrial species to facilitate vision in optical media with different refractive indices. Frogs and toads (Amphibia: Anura) are ecologically diverse, with many species shifting from aquatic to terrestrial ecologies during metamorphosis. We quantified lens shape and relative size using 179 micro X-ray computed tomography scans of 126 biphasic anuran species and tested for correlations with life stage, environmental transitions, adult habits and adult activity patterns. Across broad phylogenetic diversity, tadpole lenses are more spherical than those of adults. Biphasic species with aquatic larvae and terrestrial adults typically undergo ontogenetic changes in lens shape, whereas species that remain aquatic as adults tend to retain more spherical lenses after metamorphosis. Further, adult lens shape is influenced by adult habit; notably, fossorial adults tend to retain spherical lenses following metamorphosis. Finally, lens size relative to eye size is smaller in aquatic and semiaquatic species than other adult ecologies. Our study demonstrates how ecology shapes visual systems, and the power of non-invasive imaging of museum specimens for studying sensory evolution.